The unnatural history of the sea - Roberts, Callum (Island Press/Shearwater Books, 2007)
"Drawing on firsthand accounts of early explorers, pirates, merchants, fishers, and travelers, the book recreates the oceans of the past: waters teeming with whales, sea lions, sea otters, turtles, and giant fish. The abundance of marine life described by 15th century seafarers is almost unimaginable today, but Roberts both brings it alive and artfully traces its depletion. Collapsing fisheries, he shows, are simply the latest chapter in a long history of unfettered commercialization of the seas."--Jacket